Weapons of choice: the effect of natural resources on terror and insurgencies - Dreher, Axel; Kreibaum, Merle (Journal of peace research, 2016)
This article investigates the effect of natural resources on whether ethno-political groups choose to pursue their goals with nonviolent as compared to violent means, distinguishing terrorism from insurgencies. It is hypothesized that whether or not the extraction of fossil fuels sparks violence depends both on the group’s characteristics and the state’s reaction. Data are taken from the Minorities at Risk Organizational Behavior (MAROB) project, covering 118 organizations in 13 countries of the Middle East and North Africa over the 1980-2004 period. The multinomial logit models combine group- and country-specific information and show that ethno-political groups are more likely to resort to rebellion rather than using nonviolent means or becoming terrorists when representing regions rich in oil. This effect is enhanced for groups already enjoying regional autonomy or being supported by a foreign state but can be mitigated by power-sharing arrangements. These results are thus in line with the argument that economic considerations, or ‘greed’, dominate over political considerations, or ‘grievances’, with regard to violent conflicts. The opposite appears to hold considering terrorism, as we do not find any evidence for a resource curse here, but find an increasing effect of political discrimination and a decreasing effect of regional autonomy.